Les priorités de recherche sur la santé des francophones en Ontario - Chomienne, Marie-Hélène; Luyinga, A.; Farmanova, Elina (Bureau des services en français du Ministère de la santé et des soins de longue durée de l’Ontario et Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2011)

Les priorités de recherche sur la santé des francophones en Ontario - Kalay, Anifa L.; Chomienne, Marie-Hélène; Farmanova, Elina (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)

Les Franco-Ontariens âgés souffrant de maladies chroniques se perçoivent-ils bien desservis ? Une étude exploratoire de l'impact de la situation linguistique minoritaire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Le médecin de famille canadien, 2012)
Dans une étude exploratoire pour le compte du Consortium national de formation en santé, nous avons exploré l’impact des barrières linguistiques perçu par des personnes âgées francophones vivant en Ontario dans 3 régions différentes et souffrant d’une ou de plusieurs maladies chroniques. Notre étude, basée sur des entrevues semi-dirigées auprès de 25 personnes âgées (13 hommes et 12 femmes) souffrant de maladies chroniques, nous a permis de cerner des impacts particuliers sur la perception de la qualité des soins reçus par cette population en rapport aux enjeux de langue et de littératie.

Do chronically ill, elderly Francophone patients believe they are adequately served by Ontario’s health care system? Exploratory study of the effect of minority-language communities - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Canadian Family Physician, 2012)
In an exploratory study conducted on behalf of the Consortium national de formation en santé, a Canada-wide umbrella organization bringing together 11 postsecondary institutions that deliver training programs in various health disciplines in French, our research team explored the effect of language barriers perceived by elderly Francophone patients living in 3 different regions of Ontario with one or more chronic diseases. Our study was based on semistructured interviews of 25 elderly subjects (13 men and 12 women) with chronic diseases. It enabled us to determine the effect on the perception of the quality of care received by this Francophone population in relation to the challenges of language and literacy.

Enquête exploratoire sur le recueil de la variable linguistique dans les données administratives des hôpitaux de la région du RLISS-Champlain - Chomienne, Marie-Hélène; LeClerc, Chantale; Schnarch, Brian; Bouchard, Louise; McKay, Martine; Farmanova, Elina (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, Réseau local d’intégration des services de santé de Champlain, 2011)

Access to resources in the community through navigation: Protocol for a mixed-methods feasibility study - Dahrouge, Simone; Gauthier, Alain; Chiocchio, François; Presseau, Justin; Kendall, Claire; Lemonde, M.; Chomienne, Marie-Hélène; Perna, A.; Toal-Sullivan, Darene; Devlin, R. A.; Timony, Patrick; Prud'homme, Denis (JMIR Publications, 2019)
Background: Community-based health and social resources can help individuals with complex health and social needs achieve their health goals. However, there is often inadequate access to these resources due to a lack of physician and patient awareness of available resources and the presence of social barriers that limit an individual’s ability to reach these services. Navigation services, where a person is tasked with helping connect patients to community resources, embedded within primary care may facilitate access and strengthen the continuity of care for patients. Objective: This study aims to describe the protocol to assess whether the implementation of the Access to Resources in the Community (ARC) navigation model (an innovative approach to navigation services) is feasible, including its potential to achieve its intended outcomes, and to assess the viability of the evaluation approach. Methods: The study consists of a single-arm, prospective, explanatory, mixed-methods, pre-post design feasibility study focusing on primary care practice settings with vulnerable populations. Participants include primary care providers and patients. Results: Enrollment is closed with 82 patients. Navigation services have ended for 69 patients. Conclusions: The study of an innovative complex intervention requires an adequate assessment of the feasibility of the intended approach during which the potential challenges of the planned intervention and need for its adaptation may be uncovered. Undertaking a feasibility study of the ARC navigation model from a conceptually clear and methodologically solid protocol will inform on the practicality and acceptability of the approach, demand for the services, ease of implementation, quality of integration of the new services within primary care, and practicality and potential for efficacy prior to initiating a randomized controlled trial.